2008
DOI: 10.1080/07399330801949632
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Women's Experiences With the Use of Traditional Family Planning

Abstract: The United Nations Population Fund (UNFPA) and the Hashemite Kingdom of Jordan Ministry of Health (MOH) have identified the importance of strengthening national capacity through the integration of reproductive health (RH) services into the primary health care system. It is reported that a high percentage of Jordanian women use traditional family planning (TFP) methods, frequently using them incorrectly. Our purpose in this qualitative descriptive study was to explore the issues and challenges related to the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(78 citation statements)
references
References 19 publications
2
76
0
Order By: Relevance
“…For example, a 39-year-old mother of seven children noted, "Our prophet Mohammed said, 'Reproduce and have children as I am in the life after. I will be proud of you in front of the nations"' [20]. In another study, a Jordanian Muslim primipara said, "People start asking after the first month of marriage whether you "save anything inside your abdomen" meaning, "are you pregnant yet?"…”
Section: Significance and Backgroundmentioning
confidence: 99%
“…For example, a 39-year-old mother of seven children noted, "Our prophet Mohammed said, 'Reproduce and have children as I am in the life after. I will be proud of you in front of the nations"' [20]. In another study, a Jordanian Muslim primipara said, "People start asking after the first month of marriage whether you "save anything inside your abdomen" meaning, "are you pregnant yet?"…”
Section: Significance and Backgroundmentioning
confidence: 99%
“…The adaptation corresponded to an increase in two questions about social-historical context and ethical aspects in domain [2,17]. In the criteria analysis, all studies explained the social-historical context, guide themes, identified set of categories and inductive character of analysis [18][19][20][21][22][23][24][25][26]. Eight studies reported about how participants were selected [19][20][21][22][23][24][25][26].…”
Section: Critical Assessment Of the Articlesmentioning
confidence: 99%
“…In the criteria analysis, all studies explained the social-historical context, guide themes, identified set of categories and inductive character of analysis [18][19][20][21][22][23][24][25][26]. Eight studies reported about how participants were selected [19][20][21][22][23][24][25][26]. Six mentioned type of analysis [20,[22][23][24][25][26] and five notified how many researchers analyzed the data [20][21][22]25].…”
Section: Critical Assessment Of the Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported on the relatively low utilization of PPHC (60%) was related to lack of knowledge and perception of need related to available health care services. A recent study documented Jordanian women's experiences with the use of traditional family planning and identified the importance of competent and knowledgeable HCPs to help them make informed choices (Khalaf et al. 2008).…”
Section: Literature Reviewmentioning
confidence: 99%